ETHNOPHYSICAL INTEGRATION IN COOPERATIVE LEARNING BASED ON JAVANESE CULTURE TO IMPROVE GENERIC SCIENCE SKILLS AND STUDENT SELF-EFFICACY - Putri Srijayanti; Derlina Derlina (Universitas Negeri Medan, 2020)
Research this aiming to improve generic science skills and student self-efficacy through a Javanese culture-based cooperative learning model with the Culturally Responsive Teaching approach. Research this do in MAS UIN Laboratory Medan SU TP 2018/2019. This type of research is a quasi-experimental exercise using two groups of pretest-posttest design. The research sample is class X MIA 1 as the experimental class and class X MIA 2 as the control class. The instrument used was a generic science skill test instrument and student self-efficacy questionnaire. The data in this study were analyzed using the t-test and gain test. The results of the study showed that the generic science skills and self-efficacy of students who were taught by cooperative learning models based on Javanese culture were better than students who were taught with conventional models. Results research to show learning physics through approach Culturally Responsive Teaching is integrated ethnophysics could develop KGS on direct observation skills, logic inference, and abstraction while student self-efficacy increases aspects of achievement and self-motivation, as well as self-discipline